Evaluation of the Effect of Transcutaneous Electrical Nerve Stimulation on Postoperative Pain in Surgical Extraction of Impacted Mandibular Third Molars: A Double Blind Randomized Clinical Trial - Arabion, Hamidreza; Kazemi, Hamid; Dehganian, Yaser; Ebrahimi, Reyhaneh; Tabrizi, Reza (Regeneration, Reconstruction & Restoration (Triple R), 2017)
Introduction: Transcutaneous electrical nerve stimulation (TENS) has been used to reduce post-operative pain. The aim of this study was to assess the efficacy of TENS as an adjunctive pain relief measure after impacted third molar surgery. Materials and Methods: In this double-blind randomized clinical trial, patients requiring surgical extraction of third molars (Class 2 and B of Pell and Gregory) were randomly divided into two groups. Group I subjects received TENS immediately after surgery along with analgesics (400 mg Gelofen). In group II, patients received 400 mg Gelofen immediately post-operation (control group). The pain intensity was evaluated using a visual analog scale (VAS) eight hours after surgery. The independent t-test was applied to compare pain intensity between the two groups. Results: Three-hundred subjects were studied in two groups (each group had 150 participants). The mean pain intensity score was 3.7±1.43 in group I and 4.36±1.66 in group II. A significant difference was noted for pain intensity between the two groups (P=0.001). Conclusion: Use of TENS may decrease pain intensity during the first eight hours after impacted third molar surgery and may obviate the need for additional doses of non-steroidal anti-inflammatory drugs (NSAIDs).